The Effect of Intranasal Desmopressin Spray on Basal and Total Tear Secretions in Healthy Subjects (Nigerian Journal of Physiological Sciences, 2021)
Summary: Many hormones have been implicated in dry eye syndrome. This study was carried out to investigate the effects of antidiuretic hormone (ADH) on tear secretion. Fifty (50) healthy male and female volunteers between the ages of 21 and 70 years were studied. They were given exogenous ADH in the form of intranasal desmopressin spray (DDAVP). Total and basal tear secretions were assessed using the Schirmer strip at baseline and at 30 minutes intervals for a period of 180 minutes after the nasal administration of 10 μg desmopressin spray into each nostril. Blood samples were taken before and 60 minutes after desmopressin administration for the determination of plasma osmolality and plasma ADH concentrations. Results showed a significant reduction (p
Keywords: Tears; Desmopressin; Osmolality; Antidiuretic hormone; Schirmer strip; Lacrimal gland